2008
DOI: 10.1007/s00419-008-0268-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geometry on separation efficiency in a hydrocyclone

Abstract: A numerical study of the gas-liquid-solid multiphase flow in hydrocyclones is presented. Three models of turbulence, the RNG k-ε model, the Reynolds stress model and Large eddy simulation with the volume of fluid model (VOF) multiphase model for simulating air core are compared in order to predict axial and tangential velocity distributions. This presentation is mainly aimed at identifying an optimal method, used to study effective parameters, based on which, eventually, effect of inlet flow rate variations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Several studies have been reported in the literature related to the separation process using hydrocyclones: Cullivan et al [5]; Petty and Parks [6]; Simões [7]; Brennan et al [8]; Delgadillo and Rajamani [9]; Sripriya et al [10]; Zhao et al [11]; Farias et al [12]; Martínez et al [13]; Mousavian and Najafi [14]; Wang and Yu [15]; Buriti [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in the literature related to the separation process using hydrocyclones: Cullivan et al [5]; Petty and Parks [6]; Simões [7]; Brennan et al [8]; Delgadillo and Rajamani [9]; Sripriya et al [10]; Zhao et al [11]; Farias et al [12]; Martínez et al [13]; Mousavian and Najafi [14]; Wang and Yu [15]; Buriti [16].…”
Section: Introductionmentioning
confidence: 99%
“…To model anisotropic turbulence problems, turbulence models like the Reynolds stress model (RSM) or Large eddy simulation (LES) should be used, which can both give results comparable to the experimental measurements (Brennan, 2006;Mousavian and Najafi, 2009;Wang and Yu, 2006). For computational efficiency, the RSM model combined with a standard wall function is here adopted, similar to the CFD-DEM and CFD-LPT modelling of DMC Wang et al, 2009a):…”
Section: Model Descriptionmentioning
confidence: 98%
“…e upper and lower limits of the inlet velocity of the same hydrocyclone will be different under different physical parameters. Rietema suggested that the lower limits of the inlet velocity is determined by static pressure loss and the upper limits of the inlet velocity is determined by the centrifugal head [12], and many experiments have determined the maximum limit with respect to the separation efficiency [13,14]. In recent years, Zhang et al suggested that the lower limit is ascertained by the flow field stability and the upper limit is largely determined by the energy consumption [15].…”
Section: Introductionmentioning
confidence: 99%